Responsible management education - Arbaiza Ríos, Maritza; Arruda Filho, Norma de Paula; Carrión Puelles, Naldi S.; Estrada-Merino, Alfredo; García de la Torre, Consuelo Aledaila; González Gutiérrez, Victoria; Fructuozo Loiola, Gustavo; Molina, Christiane; Sanabria Villanueva, Jorge; Stuart Alvarado, Patricia; Yepes-López, Gustavo Adolfo (Routledge, 2021)
This book chapter discusses the background of the Principles for Responsible Management Education (PRME) Chapter for Latin America and the Caribbean, its actions, and achievements since its foundation that dates to 2011. With more than seven years of work and members from 16 countries in the Latin American region, this PRME Chapter has worked extensively in all six principles of PRME. This section of the book also presents some of the research that has been developed as joint efforts from the members of the Chapter. In addition, this part of the book lays out some of the plans for the future of the group.
PRME chapter Latin America & The Caribbean
Keywords: Background; Responsible; Management education; Campus Mexicali